Genomic testing in early stage invasive male breast cancer: An NCDB analysis from 2008 to 2014. Issue 3 (25th April 2019) - Dubrovsky, Esther; Raymond, Samantha; Chun, Jennifer; Fong, Amy; Patel, Nisha; Guth, Amber; Schnabel, Freya
Abstract: Purpose: Genomic assays, or tissue gene profiling tests, are widely used to predict recurrence of early stage invasive breast cancer and guide systemic therapy. The purpose of our study was to examine the current national trends of genomic testing in male breast cancer (MBC) and its association with systemic therapy. Materials and Methods: The National Cancer Database (NCDB) includes 6227 cases of pathologic T1/T2 and N0/N1 MBC from 2008 to 2014 with known genomic testing status. Results of the tests were grouped as low, intermediate, and high risk of recurrence scores (RRS). Statistical analysis included multivariate logistic regression and Chi‐square tests. A supplemental analysis in female breast cancer was provided as reference. Results: Of the 6227 cases of MBC age 18‐90, 1478 (23.74%) underwent genomic testing. Testing was significantly associated with age, race, tumor grade, year of diagnosis, receptor status, and nodal status. Distribution of RRS in MBC was 59.3% low, 27.4% intermediate, and 13.3% high. RRS in men were significantly associated with tumor grade and size, but not nodal status. Those with a low RRS were 7‐times more likely to be treated with hormone therapy alone (AOR 7.18, CI 5.78‐8.91, P < 0.001). Those with a high RRS were five times more likely to receive a combination of hormone and chemotherapy (AOR 5.16, CI 3.60‐7.40, P < 0.001). Conclusion: Rates of testing and distribution of RRS in men and women with early stage invasive breast cancer are similar. Treatment patterns in MBC varied significantly based on genomic testing results, even when adjusted for other clinicopathologic features. Further investigation is required to determine the prognostic and predictive nature of genomic testing in male breast cancer.